Uşak tekstil sanayinin üretim ve pazar yapısının analizi - Çevik, Gürbüz (Fen Bilimleri Enstitüsü, 1995)
Uşak; Ege bölgesinde 38* İ 2' ve 39*50' kuzey enlemleri ile 28*48' ve 29*57* doğu boylanılan arasında yer alan bir şehrimizdir. îlin genel ekonomik durumu incelendiği zaman sanayinin ön planda olduğu görülmektedir. Sanayi toprak ve tekstil olmak üzere 2 ana sektör üzerine kuruludur. Tekstil sektörünün 3 ana merkezde toplandığını görmekteyiz. Karahallı ilçesinde dokumacılık, Eşme ilçesinde kilimcilik ve il merkezinde ise hemen hemen bütün tekstil dallan ile üretim yapılmaktadır. Karahallı ilçesinde 1910' lu yıllardan beri dokumacılık işinin var olduğu bilinmektedir. Önceleri el tezgahlan ile başlayan dokumacılık, ilçeye Bursa yapımı tezgahların gelmesiyle mekanize olmuştur. Günümüzde bulundurduğu tezgahlar itibariyle oldukça eski teknolojiye sahiptir. Eşme ilçesinde dünyaca ünlü, kök boya ile boyanmış, özgün motifler ile süslü elde dokunmuş kilimler üretilmektedir. II merkezi, 1950' li yıllarda ülkemizin önde gelen tekstil merkezlerinden biri iken, günümüzde eski önemini kaybetmiş ve kendini yenileyememiştir. Uşak ilini bir bütün olarak ele aldığımız zaman, sektörün eski makina parkuruna sahip olması, teknolojik gelişmelere ayak uyduramaması, teknik eleman azlığı, kalite kontrole önem verilmeyişi, düşük kapasitede ve verimde çalışılması gibi özelliklere sahip olduğu dikkati çekmektedir.

The city Uşak is located at the thereshold of interior Western Anatolia and the city name as " UŞŞAK " in old documents " UŞŞAK " is an Arabic origin word meaning *f Loverds Land *\ With a law produced on 15 th July, 1953 name of the city was announced as " UŞAK '\ In the environment of the city Uşak which has a very long history» there are various remains like " Antique Sebaste **, "Blaundos" towns and Selçikler Mound which all witnessed many and different historical periods and civilizations. According to the first enumaration made in 1913, in the period of Ottoman Empiremcnt» it was found that 3 of total 13 manufacturers who deal with wool thread and wool weawing all over the country were in Uşak. The economy of Uşak is mainly based on agriculture and industry. The land utilized for agriculture, including its counties is 242,144 hectare. Since watering opprtunitics arc limited (13,427 heetars), agriculture is not a developed sector and eventually a trend towards industrialization has been observed in Uşak. The most notcworty example of this, Turkey* s first sugar production factory was established in 26 November» 1926 by local investors. The livelihood rcssourcc of Karahalh in Uşak is weawing trade, agriculture and party cattle-dealing. The history of weawing in Karahalh very old. Previosly, there was hand-wewing in the years of 1950s it was mechanized. Even it could not keep in step with developing techonology the biggest part of the unbleached muslin of printed cloth is being weawed in town of Karahalh. Generally cotton cloth is being produced. Weawing occupies a very important place in the economic life of Karahalh. Weawing is a family enterprise. People of Karahalh travel every part of the country for exhibiting their weaved products. V11X Agriculture has the primaly role in Eşme country. In Eşme besides agriculture kilim wcawing is also wide-spread. The Eşme Kiliras which were weaved for personal needs in the past and today which could only be seen in mosques arc grouped generally as: ** Altınbaş, Toplu, Hürriyet, Al baş and Selvili Namazlağ tf Besides these " Gıcıklı " is also known type. Textile and ceramic sectors are the leading industries in Uşak and constitute a big economic potential. Ceramic sectors are two companies, producing 4.000.000 square meter floor and wall tiles. Textile sector is mainly separated into 5 groups. 1. Yarn production 1.1. Synthetic and cotton yarn production 1.2. Woolen yarn production 1.2.1. Kammgarn yarn production 1.2.2. Streichgarn yarn production 2. Fabric production 2.1. Cotton fabric production 2.2. Woolen yarn production 2.2.1. Plush blanket production 2.2.2. Kilim production 2.2.3. Carpet production 3. Dyeing-Finishing-Printing 4. Warp knitting 5. Leather production and leather clothing Synthetic and cotton yarn production sector, 16 factories with a capacity of 3000 tons/annual have achieved a global production of 7450 tons/ annual. ( 5 Ring factories with a capacity of 3500 tons/annual have achieved a global production of 3200 tons/annual. 1 1 Open-End factories with a capacity of 4500 tons/annual have achieved 4250 tons/annual.) Woolen yarn production sector, approximately 161 streichgarn yarn and 1 kammgarn yarn factories (Table 2) operating in the main country have a total production capacity 60000 tons. The global production of 1994 is 45000 tons. Due to the economic crises during the II. Word War, carpet production which is one of the leader export products of Uşak went through as stagnation period. As a result, manual cotton weawing looms were used to supply the needs of the domestic markets. Howewer in time, the utilization of demostically produced automatic ix looms improved and developed the cotton fabric production sector in Uşak.(Tabie 3.) In the recent years, a rapid increase in plush blanket production has been observed due tö the gcvorment subsidies* At the present, there are 34 factories operating in this sector and their total annual production capacity is 2.5 million pieces ? As of 1994, their global production 2.25 million blankets. A potion of the output is sold in the domestic markets and some are exported* Kilims production sector, which has capacity of production 200.000 meter/so; of machine made kilims, 10 factories and 65 workshop are operating. Their global production as of 1994 is 155.000 metcr/sq. Carpet production sector, which has capacity of production 5.500 nrVday of maschine made carpets. 15 factories are operating. Their global production as of 1994 is 4.850 m3/day. In 1994, 27 operations are processing fabric in Uşak. The annual dyeing-finishing-printing capacities of these operations arc 50 million meters. Warp Knitting sector, İ companies has achieved a global production of 75.000 m/annual. Table 5, Warp knitting machines in Uşak city MACHINE PRODUCTION YEAR NUMBER OF MACHINE Kândler İ 994 İ Boegli 1983 -> There arc approximately 250 companies active in the leather sector. Leather processing is mostly based on shep/goat leather and annually 30 million pieces of raw leather is processed which constitucs 70% of the total leather production of Turkey. The processed leathers are then sent to Istanbul and Izmir cities for ready-made clothing production such as skirts, overcoats and jackets are most exported. In the recent years, ready-made leather clothing sector has devoloped rapidly. Today there are approximately 100 ready-made leather clothing workshops and they are producies 400 pieces per day. a 1992 01934 PROCESSED LEATHER READY-MADE LEATHER CLOTHING Figure 1. Increasing number of leather companies To increase the potential for production, the present companies have been enlarged with the addition of new machines and new companies are being established in Uşak, *L ö 3000 1992 1994 Figure 2» Incrcsing number of worker in leather compannies The city is also active in the trade busines parallel to its active industiy. The goods manufactured ( processed leather, ready-made leather clothing, carpet and textile goods etc. ) arc marketed to businessmen coming to Uşak throughout Turkey.
Production and marketing analyse of the textile industry in Uşak
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Keywords: piyasa analizi; tekstil endüstrisi; uşak; market analysis; textile industry; uşak